Drying treatments on Chinese yam (Dioscorea spp.) prior to wet milling influence starch molecular structures and physicochemical properties. (May 2020) - Duan, Xu; Han, Huaxin; Deng, Renpan; Wu, Peng
Abstract: The molecular structures and physiochemical properties of starches isolated from Chinese yam ( Dioscorea spp. ) slices with various drying treatments (including hot air-drying at different temperatures, microwave freeze drying and ultrasonically enhanced hot air-drying) prior to wet milling were examined. The average whole molecular size ( R h ¯ ) and debranched amylopectin chain length ( X ¯ ) were significantly decreased whereas the amylose chains and content presented negligible changes after drying. These structural modifications are consistent with the observed higher pasting viscosity, lower gelatinization temperatures and enthalpy changes, and greater digestion rate and extent for the dehydrated yam slices compared to that for the fresh yam. Among the drying techniques applied, the microwave freeze drying (MFD) resulted in the greatest amylopectin degradation with the smallest R h ¯ and X ¯ along with the largest amount of short amylopectin chains (DP 6–12) due to the highly intensive moisture removal process. Correspondingly, the MFD contributed to the lowest gelatinization temperatures and enthalpy changes while the highest digestibility. The molecular degradation generally increased with increasing hot air-drying temperature, agreement with the corresponding functional changes. The structure-property correlations indicates the significant roles of starch molecular structures in controlling the drying-induced physicochemical changes. This study can be used to suggest ways in which some improved functional properties of yam starch-based products can be obtained through optimal drying techniques. Graphical abstract: Image 10936 Highlights: Drying treatments affected molecular structures and functional properties of yam starch. MFD caused greatest amylopectin degradation with highest digestion rate and extent. Molecular degradation generally increased with increasing hot air-drying temperature. Amylopectin fine structures dominated drying-induced physicochemical changes. Negative correlations between average chain length and pasting viscosity and digestion rate.